2021
DOI: 10.1111/beer.12408
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impetus for internal CSR Practices with digitalization strategy in the service industry during COVID‐19 pandemic

Abstract: The year 2020 began with a glimpse into the darkness with the onset of the worldwide COVID-19 pandemic. An invisible, threatening virus has forced many countries to practice restricted movement and impose lockdowns for the sake of their citizens' safety and well-being. In response, many business organizations have implemented various remote-work arrangements. These arrangements have spurred the use of digitalization strategies and have landed many employees in the vulnerable virtual workplace. With employees f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 86 publications
1
21
0
Order By: Relevance
“…Regarding the methodological implications, and according to the reviewed articles in the present paper, it appears that future research would highly benefit from employing ethnographic methods [61], longitudinal studies [59,88,94,98], comparative and crosscultural research [67,80,83,85], experimental research design [57], and data collecting from different sources [84,87], specifically relying more on the employees rather than senior managers' perspectives [47,48]. However, these methodological recommendations mostly come from those quantitative studies that originated from utilitarian philosophies.…”
Section: Implications For Context and Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding the methodological implications, and according to the reviewed articles in the present paper, it appears that future research would highly benefit from employing ethnographic methods [61], longitudinal studies [59,88,94,98], comparative and crosscultural research [67,80,83,85], experimental research design [57], and data collecting from different sources [84,87], specifically relying more on the employees rather than senior managers' perspectives [47,48]. However, these methodological recommendations mostly come from those quantitative studies that originated from utilitarian philosophies.…”
Section: Implications For Context and Methodsmentioning
confidence: 95%
“…Individual outcomes of SRHRM practices have been the most topical issue addressed by previous studies. In this regard, a considerable number of studies confirmed that SRHRM can have a positive impact on employee commitment [21,49,63,66,78,83,87,95,97]. Other individual factors positively affected by SRHRM practices include employee citizenship behavior [51,55,62,66,83,84,92], employee task performance [59,94], employee satisfaction [72,81,95], employee well-being [68,78], employee loyalty [101], the propensity of employees to identify themselves with their organization [59,83,88,89,91], employeeemployer relationships [79,84], employee trust in the firm [72,74,76], employee empathy [52], employee knowledge sharing behavior [74], employee innovation behavior [54,99], and employee intrapreneurial behavior [96,98,99].…”
Section: Outcomes Of Srhrmmentioning
confidence: 98%
See 1 more Smart Citation
“…As organizations are facing increasing uncertainty from various sources, for example, the COVID‐19 pandemic (Low & Bu, 2021), ways to navigate these vast challenges and ultimately achieve a win‐win relationship between employees’ performance and well‐being have received substantial attention in both academia as well as in practice (Carnevale & Hatak, 2020; Salas‐Vallina et al, 2021). While employees’ performance is generally treated as the cornerstone of organizational survival, now their well‐being is also being viewed as vital not only for their own further development but also for organizations’ long‐term success (Wood & Ogbonnaya, 2018; Wright & Huang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As organizations are facing increasing uncertainty from various sources, for example, the COVID-19 pandemic (Low & Bu, 2021), ways to navigate these vast challenges and ultimately achieve a win-win relationship between employees' performance and wellbeing have received substantial attention in both academia as well as in practice (Carnevale & Hatak, 2020;Salas-Vallina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%